Integration of Pancasila Student Profile Values and Religious Moderation in Multicultural Education at SMA Muhammadiyah 10 Surabaya - Izuddin, Azmi; Hayumuti, Hayumuti; Bakhruddin, Mukhammad (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the integration of Pancasila Student Profile values and religious moderation in multicultural education at SMA Muhammadiyah 10 Surabaya. This study uses a qualitative descriptive approach with the Semi-Structured Interview method, where data is collected through in-depth interviews with 3 groups. Among them are the vice principal who is also the main figure in implementing religious moderation, students as representatives of various religions, and school staff as well as direct observation of educational activities at school. The purpose of this study is to analyze the integration of Pancasila student profiles with religious moderation in multicultural education. The results of the study show that the integration of both in multicultural education is an effort to synchronize in the implementation of inclusive learning. Teachers' understanding of the concept of religious moderation is an important point in creating a tolerant environment. Through learning, extracurricular activities and daily school life, teachers convey knowledge transfer that is closely related to multicultural education. In addition, the implementation of broad-based education with derivatives emphasizes accepting students from all walks of life, every child has the right to succeed, and education adjusts to students' passions are the main factors in running education at SMA Muhammadiyah 10 Surabaya. It is concluded that multicultural education is an important concept and must be understood and mastered by teachers so that it can make students have a high enthusiasm for learning without looking at differences in conditions and backgrounds.